Fodor's 2009 Boston. - Fodor's Travel Publications, Inc. (New York : Fodor's Travel Pub., 2009)
A travelers' guide to Boston that presents details on the history of the city, sites to see, lodging, dining, activities, and side trips, also providing itineraries and a pull-out street map.
"Pullout map inside"--Cover.
Cover title: Boston 2009.
Includes index.
Young Adult
Keywords: Boston (Mass.) -- Guidebooks; Boston (Mass.) -- Guidebooks